Опис властивостей деформацiї парно-парних iзотопiв 102−106Pd - Waheed, M. O.; Sharrad, F. I. (Publishing house "Academperiodika", 2018)
A description of the even-even Pd isotopes for A = 102 to 106 in the framework of the Interacting Boson Model (IBM) are carried out. The low-lying positive parity yrast bands, as well as the associated B(E2) values, have been calculated in good agreement with the experimental data. The contour plots of the potential energy surface are studied, by using the simplified form of IBM with an intrinsic coherent state. The critical points have been determined for 102Pd isotope, and O(6) symmetry is substantiated for 104,106Pd.